Effects of Dietary Medium-Chain Triglyceride Supplementation on the Serum Metabolome of Young Adult and Senior Canines - Yuanlong Pan; Miriam Sindelar; Ethan Stancliffe; Leah P. Shriver; Rondo P. Middleton; Gary J. Patti (Animals)
In dogs, brain aging may lead to cognitive decline and cognitive dysfunction syndrome (CDS) [...]